Self-assembly of transition-metal-oxide nanoparticle supraparticles with designed architectures and their enhanced lithium storage properties. Issue 41 (3rd October 2016) - Guo, Guannan; Ji, Li; Shen, Xiudi; Wang, Biwei; Li, Hanwen; Hu, Jianhua; Yang, Dong; Dong, Angang
Abstract : Hollow structured transition-metal-oxide nanoparticle supraparticles are designed for high-performance lithium storage. Abstract : Self-assembled nanoparticle (NP) superlattices consisting of close-packed NPs represent a new type of solid-state materials that have been widely used in thin-film electronic and optoelectronic devices. The ability to engineer the architecture of NP superlattices is critical to expand their applications beyond electronics and optoelectronics. Transition metal oxides (TMOs) such as Fe3 O4 are earth-abundant and environmentally benign materials with rich electrochemical properties. Herein, we report the emulsion-based assembly of TMO NP supraparticles with or without hollow interiors by manipulating the oil/water interfacial tension, which can be realized by controlling the concentration of the surfactant. Using Fe3 O4 NPs as a model system we show that the original organic ligands attached to the NP surface can be transformed into a three-dimensional interconnected carbon network by in situ heat treatment, resulting in carbon-coated NP supraparticles that are particularly suited for energy storage applications. When evaluated as an anode material for lithium-ion batteries, the carbon-coated, hollow Fe3 O4 NP supraparticles exhibit significantly enhanced lithium storage properties when compared with their solid counterparts as well as most Fe3 O4 -based anodes reported previously. The superior electrochemical performance of hollow NP supraparticles benefits from their hollow interiors, conformal carbon coating, and close-packed configuration of NPs.